Population structure of the Caspian shad (Alosa braschnikowi Borodin, 1904) in the southern coast of the Caspian Sea between Gomishan and Miankaleh regions - Omid Jafari; Ali Shabani; Hamed Kolangi Miandare (تاکسونومی و بیوسیستماتیک, 2014)
The present study was carried out to determine population structure of Alosa braschnikowi, one of the endemic species in the Caspian Sea, with five polymorphic microsatellite loci (AsaD030, AsaD042, AsaC249, AsaD312, AsaC051). Fifty six specimens of A. braschnikowi were collected from Gomishan and Miankaleh (28 specimens for each population) in Golestan province. The results showed that the average observed heterozygosity for Gomishan and Miankaleh were 0.536 and 0.514, respectively, with an average of 0.525 for the two populations. The number of observed alleles per locus ranged from 8 to 17 with an average of 12.4 alleles. Average number of effective allele in Gomishan and Miankaleh was calculated 8.53 and 7.61. Also, in eight cases of 10 tests in Hardy-Weinberg equilibrium there was statistically significant deviation (P<0.001). The average amount of gene flow and Fis were 17.34 and 0.395, respectively. The Fst value was 0.016 which was indicative of the low genetic differentiation between the Gomishan and Miankaleh populations that could be due to the natural migration of the fishs. The results for molecular variance analysis based on Fst index, exhibited that genetic diversity within population was only 1 percent and among populations was 99 percent. The results of present study showed that although the genetic diversity of A. braschnikowi in Golestan province was appropriate, it is possible that genetic bottleneck will arise in future years.